Hand hygiene compliance in intensive care units: An observational study. Issue 2 (31st October 2019) - Hoffmann, Magdalena; Sendlhofer, Gerald; Gombotz, Veronika; Pregartner, Gudrun; Zierler, Renate; Schwarz, Christine; Tax, Christa; Brunner, Gernot
Abstract: Aim: Health care–associated infections along with antibiotic resistance are a leading risk for patient safety in intensive care units. Hygienic hand disinfection is still regarded as the most effective, simplest, and most cost‐effective measure to reduce health care–associated infections. To improve hand hygiene compliance and to prevent health care–associated infections, interventions of the "German Clean Hands Campaign" were implemented in a university hospital. Methods: Observational single‐center study using direct observation and feedback. Hand hygiene performance was assessed in 12 intensive care units between 2013 and 2017. Linear mixed model regression analyses were used to estimate the compliance trend over time. Results: In total, 10 315 "my five moments for hand hygiene" were observed. The mean hand hygiene compliance rates increased from 75.1% to 88.6% during the study period, yielding an estimated increase of about 4.5% per year. However, there are differences in compliance between occupational groups (physicians: between 61.2% and 77.1%; nurses: between 80.2% and 90.9%; others: between 61.3% and 82.4%). Conclusions: After implementation of the "German Clean Hands Campaign" interventions, an overall significant improvement of hand hygiene was detected. Compliance measurements helped to raise awareness among health care professional groups. SUMMARY STATEMENT: What is already known about this topic? A significantly higher prevalence of infections has been observed in intensive care unit patients compared with patients in other wards. Hygienic hand disinfection is still regarded as the most effective, simplest, and most cost‐effective measure to reduce health care–associated infections. Low hand hygiene rates in intensive care units are a major problem for patient safety. What is already known about this topic? Implementation of the "German Clean Hands Campaign" showed continuous improvement in hand hygiene for all health care professionals in intensive care units over a period of 5 years. There are differences in compliance rates between health care profession and intensive care unit types. Pediatric intensive care units had the highest hand hygiene compliance rates. The implications of this paper: Overall, hand hygiene compliance in intensive care units increased over a period of 5 years after continuous campaigning, training, observation, compliance measurements, and direct feedback. It is necessary to raise awareness for hand hygiene in a repetitive manner within all health care professional groups now and in the future. Because of the differences in compliance rates between health care professionals, more tailored and evidence‐based interventions should be implemented.